SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMAAN BEASISWA DI UNIVERSITAS PERSADA INDONESIA YAI MENGGUNAKAN FMADM - Gustina, Dian; Malays, Essy; Ichsan, Adi Nur (Jurnal Pilar Nusa Mandiri, 2012)
In accordance with regulations prescribed by the University of Indonesia YAI Persada to obtain a scholarship, it is a necessary criterion to determine who will be selected to receive a scholarship. The scholarship conducted by several agencies to help someone who is less fortunate or achievement for the determination to take studying. For assistance in determining a person who deserves the scholarship, it needed a support system decision. Fault one method that can be used for Decision Support Systems is using Fuzzy MADM (Multi-Attribute Decision Making). This research will be lifted a case of finding the best alternative based on criteria that have been determined to use traditional methods of SAW (Simple Additive weighting) to perform calculations FMADM method in that case. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case, meant that alternatives are eligible to receive scholarships based on specified criteria. Research carried out by finding the weights for each attribute value, then do ranking process that will determine the optimal alternative, which is the best student.